Environmental geology and isotopic evaluation of springs within the central part of the Sierra Cerro de La Silla, northeastern México. (November 2022) - Pantoja-Irys, Jerjes Rigoberto; Mujica-Sánchez, Hugo; Arista-Cázares, Luis Eduardo; Hernández-García, César Michel; Wagner, Mark
Abstract: The Monterrey Metropolitan Area (MMA), in the State of Nuevo León, México, has had a significant increase in its population and associated urban footprint for decades. From a population standpoint, it represents the second largest urban area in México. Its growth has required increasing infrastructure for the necessary services including public access to potable water, which will continue to increase over time. The supply of water resources for the metropolis comes mainly from groundwater sources. These sources are subject to certain conditions influenced by their geographical location, physiographical characteristics, and the geological environment, having a direct impact on the water recharge system of the regional aquifers. The government of the State of Nuevo León has developed an investment master plan for a water resource, outlined to be completed in 2050, which includes the construction of new dams and the setting up of additional shallow and deep production wells. With a constant annual population growth from one to five percent, additional stresses and vulnerability to this valuable resource will occur. Based on the changing demographics and additional stresses to water resources, it is essential to understand the localized natural groundwater regime extending from the precipitation recharge zones to the individual aquifers that serve the needs of the population. The following study evaluates specific aspects of the water regime (recharge zones and springs), in an area approximately 25 km south of central Monterrey, in the Santiago area of the MMA which is expected to have significant urban expansion in the future. The central portion of the Sierra del Cerro de la Silla, which constitutes the study area is a catchment and infiltration zone for meteoric water. Within the study area, five springs were identified and sampled during the dry season, and the collected spring water samples were submitted for geochemical and isotopic analyses. Field surveys, data collection and interpretation have contributed to the understanding of the water origin and associated physical-chemical characteristics during infiltration through the geological succession and ultimate incorporation into the aquifer. The characterization of the regime through a series of field surveys and the spring water characterization has determined the presence of a low enthalpy geothermal system at the depth, that has the potential to impact shallow freshwater regimes. In addition to contributing to the knowledge of the local hydrogeological system, this study can support the understanding of the vulnerability of the natural resource due to human activity and back up concepts of optimal use and protection. Highlights: Sierra Cerro de La Silla is an important and fast hydrogeological recharge zone in northeastern Mexico. Isotopic and geochemical characteristics of groundwater are well related to the different types of sedimentary rock formations within the flow regime. The low-enthalpy geothermal system "El Bañito" is described for the first time. Urbanization within the vicinity of Sierra Cerro de La Silla will deteriorate groundwater quality and availability in the aquifers.